The Role of Good Corporate Governance and Corporate Social Responsibility in Shaping the Financial Performance of IDX-Listed Mining Companies (2019–2023) - Raihan Haris Wiratama; Januar Eko Prasetio (International Journal of Applied Business and International Management, 2025)
The objective of this study is to empirically analyze the relationship between corporate social responsibility (CSR) and good corporate governance (GCG) practices with the financial performance of entities operating in the mining sector and listed on the Indonesia Stock Exchange (IDX) for the years 2019 to 2023. Financial performance is quantified through metrics including return on assets (ROA), return on equity (ROE), and net profit margin (NPM). Quantitative methods were employed in this study, specifically involving 120 firm-year observations from mining companies, incorporating total assets and debt-to-equity ratio (DER) as control variables. The results indicated that CSR significantly negatively affected ROA (B=-0.687, p=0.005) and ROE (B=-0.718, p=0.012), but did not significantly influence NPM (p=0.217). GCG had no significant impact on ROA, ROE, or NPM (all p-values 0.05). Firm size (total assets) positively influenced ROA (p=0.024), ROE (p=0.023), and NPM (p=0.011), while DER negatively affected all performance measures (p0.001). The findings indicate that while CSR may reduce short-term profitability, its long-term benefits could be valuable. Firms should balance CSR initiatives with prudent leverage management, and future research should explore long-term effects across industries and economic conditions.